1975
DOI: 10.1098/rsta.1975.0059
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of late Pleistocene-Holocene drainage of the River Thames in the eastern part of the London Basin

Abstract: Since 1967 the area of the Thames Estuary has been extensively surveyed using reflexion seismic techniques. The interpretation of these records coupled with the logs and samples from some 140 boreholes has led to the reconstruction of the Late Pleistocene/Early Holocene palaeodrainage pattern of the River Thames. The relationship of this drainage system to the tectonic pattern would indicate that there has been Late Pleistocene re-emphasis of the existing dominant structures. Also a large NW—SE trending monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It has been 816 JOURNAL OF QUATERNARY SCIENCE shown that this is a fluvial terrace system belonging to a now drowned offshore valley (D'Olier, 1975;Bridgland et al, 1993;Bridgland and D'Olier, 1995), an extension of the Thames-Medway, which, prior to the Holocene transgression, flowed northeastwards towards Clacton. Analysis of the gravel at Barling and elsewhere in the area has revealed that the higher terraces in this staircase are formed of different gravel, which contains flint and southern rocks such as Greensand chert but lacks a distinctive suite of far-travelled rocks that appears in the lower terraces.…”
Section: Regional Geological Contextmentioning
confidence: 99%
“…It has been 816 JOURNAL OF QUATERNARY SCIENCE shown that this is a fluvial terrace system belonging to a now drowned offshore valley (D'Olier, 1975;Bridgland et al, 1993;Bridgland and D'Olier, 1995), an extension of the Thames-Medway, which, prior to the Holocene transgression, flowed northeastwards towards Clacton. Analysis of the gravel at Barling and elsewhere in the area has revealed that the higher terraces in this staircase are formed of different gravel, which contains flint and southern rocks such as Greensand chert but lacks a distinctive suite of far-travelled rocks that appears in the lower terraces.…”
Section: Regional Geological Contextmentioning
confidence: 99%
“…Other notable offshore research has been carried out by D'Olier (1975;Bridgland andD'Olier, 1989, 1995), who has mapped the submerged extension of the Thames valley, which extends out into the southern North Sea off the coast of Essex (Fig. 4).…”
Section: Glacial Diversion Of the Rhine-thamesmentioning
confidence: 99%
“…(1992) and Laban (1995). Lowstand valley widths: Thames Estuary: D'Olier (1975), Maddy and Bridgland (2000), and Bridgland (2002); onshore Netherlands: Busschers et al . (2007); offshore Belgium/Netherlands: Mathys (2009), Ebbink and Laban (1996), and this study.…”
Section: Quaternary Palaeogeographymentioning
confidence: 99%